Manejo integrado del caracol manzana (pomacea canaliculata) en el cultivo de arroz bajo riego, en la zona de Simón Bolivar provincia del Guayas - Díaz Solís, Pedro Javier (2014)
The present investigation was carried out in Mr. Julia's lands Arreaga González, located in the Treasury "The Mercedes", vía Simon Bolívar km 12; left margin via the Mercedes km 8. The area possesses a humid tropical climate, with coordinated geographical of 01° 49´ south latitude and 79° 32´ longitude west. The height is 8 msnm, annual half temperature of 24,6 °C; pH of 6,7; annual precipitation of 1569,3 mm, annual heliophany of 892,7 and relative humidity of 85%. The floor is of plane topography, texture loamy franc and a regular drainage. Certified seed of rice variety INIAP was used 15 whose treatments were conformed by Methamidophos + Gathering of mass of eggs of P. canaliculata; Methamidophos + Stakes; Methamidophos + adults' of P. canaliculata Gathering; Meshes to the entrance of the channels + Stakes; Meshes to the entrance of the channels + adults' of P. canaliculata Gathering; Methamidophos; Butachlor and Witness. Methamidophos was applied in doses of 1,0 l/ha and Butachlor in doses of 5,0 l/ha. Se it used the design experimental Complete Blocks at random, with eight treatments and four repetitions, with the test of Tukey to 95% of probabilities.